Change Management in the Implementation of LearningCare in Universiti Utara Malaysia - Algaet, Mustafa Almahdi (2006)
Most educational institutions' administrators are concerned about e-learning and distance learning. University Utara Malaysia (UUM) Group Web communication application is a module of e-learning. Toward this end, University Teaching and Learning Centre (UTLC) has been made responsible in implementing e-learning in the university. The E-university committee has agreed to purchase Learningcare Learning Management System (LMS) for academic purposes. This system became operational in May 2002/2003 Semester. The value of e-learning has become widely recognized and accepted. This study aims to find out whether change management principles were used in the implementation of Learningcare. The study focuses on the adoption of Learningcare in University Utara Malaysia and the role of various players in UUM responsible for the development and implementation of Learningcare. John Kotter, eight stages of change management principles were chosen as the study change management platform. Correlation analysis was applied to test the eight dimensions of Kotter's change management principles. The results indicate that change management was applied in the implementation of Learningcare in UUM.